Attending a social event and consuming alcohol is associated with changes in serum microRNA: a before and after study in healthy adults. (17th November 2018) - ten Berg, P. W.; Shaffer, J.; Vliegenthart, A. D. B.; McCrae, J.; Sharkey, N.; Webb, D. J.; Dear, J. W.
Abstract: Purpose: Circulating microRNAs represent a reservoir for biomarker discovery. Our objective was to profile the change in human circulating microRNA associated with recreational use of alcohol at a social event. Material and methods: Blood was collected from healthy volunteers ( N  = 16) before and after recreational consumption of alcohol (ethanol). Biochemistry, hematology and ethanol measurements were performed. The change in the serum small RNA fraction was quantified by RNA sequencing. Results: Blood ethanol was undetectable at study entry in all subjects [<10 mg/dL]. After consuming alcohol the median concentration was 89 mg/dL [IQR: 71–138. Min–max 20–175]. There were no changes in biochemistry and hematology parameters. Serum RNA sequencing identified 1371 small RNA species (1305 microRNAs). There were significant increases [adjusted p -value <0.05, fold increase 2 or more] in 265 microRNAs, around a fifth of the total [median fold increase 2.3 [IQR: 2.1–2.5; Max: 3.7]]. miR-185-5p decreased following alcohol exposure [adjusted p -value <0.05, fold decrease 2 or more]. Conclusions: The microRNA composition of human serum is dynamic and environmental factors may have a significant impact. Within its context of use the fold change 'signal' of a microRNA must be large enough to negate the risk of false results due to background 'noise'.